2011
DOI: 10.1007/s00213-011-2379-0
|View full text |Cite
|
Sign up to set email alerts
|

The effect of energy drinks on cortisol levels, cognition and mood during a fire-fighting exercise

Abstract: Based on the results of this study, in situations of stress combined with physical performance, administration of an energy drink containing glucose and caffeine might be an easy to implement and cost effective way to maintain mental performance levels and to ameliorate the negative effects of stress on mood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 77 publications
(82 reference statements)
0
23
0
Order By: Relevance
“…Furthermore, there are no published works on the effects of any commercial energy drink on cortisol levels. This study found that one of the energy drinks tested (B beverage) increased salivary cortisol significantly, which requires further research, because this result is an acute effect that can actually help provide metabolic energy [56]. However, comparison of the percent increase in salivary cortisol with control revealed no significant differences in any groups, and the mixed-model ANOVA failed to show any differences between the change in cortisol levels before and after beverage intake in comparison with control.…”
Section: Discussionmentioning
confidence: 71%
“…Furthermore, there are no published works on the effects of any commercial energy drink on cortisol levels. This study found that one of the energy drinks tested (B beverage) increased salivary cortisol significantly, which requires further research, because this result is an acute effect that can actually help provide metabolic energy [56]. However, comparison of the percent increase in salivary cortisol with control revealed no significant differences in any groups, and the mixed-model ANOVA failed to show any differences between the change in cortisol levels before and after beverage intake in comparison with control.…”
Section: Discussionmentioning
confidence: 71%
“…In recent years, because of the sharp increase in the consumption of energy drinks, research has also focused on the synergistic effects of CHO with other psychoactive constituents such as caffeine. These studies have found the effects of CHO-caffeine combinations to go beyond the facilitation observed when either of these constituents is administered alone (e.g., Kennedy and Scholey, 2004;Scholey et al, , 2009Scholey and Kennedy, 2004;Sünram-Lea et al, 2012).…”
Section: Limitations and Recommendationsmentioning
confidence: 99%
“…Auditory Recall: A series of 20 words were broadcasted from a recording device with a word frequency of one word every 2.5 seconds. After completion of the recording, participants were instructed to write down as many words as they remembered (Sünram-Lea et al 2012). A different word list was used at each testing period.…”
Section: Test Batterymentioning
confidence: 99%
“…While extensive research has shown the ability of caffeine to increase arousal and improve mood, attention and reaction time, tests of caffeine effects on memory have been inconclusive (Loke 1988;Smith 2002;Nehlig 2010). Auditory recall has been reported to be increased (Young and Benton 2013) or unaffected (Terry 1986;Sünram-Lea et al 2012) by caffeine administration, and visual recall has been reported to be increased (Wesnes et al 2013). Nehlig (2010) suggested that caffeine does not significantly influence intentional learning and memory tasks, but may facilitate memory during passive learning.…”
Section: Introductionmentioning
confidence: 99%